1940
DOI: 10.1128/jb.39.5.609-630.1940
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Practical Classification of the Monilias

Abstract: having been suggested previously by workers in other laboratories. Since many strains were unavailable, both synonymies were based chiefly on descriptions found in the literature. The confusion caused by the use of such methods is well illustrated by Dodge (1935), who splits into 5 different genera (Syringospora, Blastodendrion, Zymonema, Castellania, and Candida), those 51 fungi in regard to which there is complete agreement between Langeron and Guerra (1938) and Ciferri et al. (1938) that they all belong to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1940
1940
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Mickle and Jones (185), Martin and Jones (178) and Conant (55) were able to confirm the results of Negroni and Mackinnon and offer some special points of interest. These workers did not start with old laboratory cultures which already had or may have started to undergo spontaneous variation but with strains freshly isolated from the human body.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Mickle and Jones (185), Martin and Jones (178) and Conant (55) were able to confirm the results of Negroni and Mackinnon and offer some special points of interest. These workers did not start with old laboratory cultures which already had or may have started to undergo spontaneous variation but with strains freshly isolated from the human body.…”
mentioning
confidence: 52%
“…An especial advance was also made by Martin, Jones, Yao and Lee (179), whose clear-cut classification of the "medical monilias" reduced to 6, the 40 species of Castellani. This classification was later improved (178). Clear-cut evaluation of techniques and criteria are characteristic of both of these papers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was conceivable that cultures maintained on different media for varying periods of time might become partially dissociated and be described as new species because of slight morphologic variations. Such a condition was found to exist when Martin and Jones (1940) studied many old cultures which could not be identified readily with the six species most commonly isolated from man: Candida albicans, C. tropicalis, C. pseudo-tropicalis, C. krusei, C. parakrusei, and C. stellktoidea. Before these cultures could be identified by the methods of Martin, Jones, Yao and Lee (1937) it was necessary to streak 48-hour Sabouraud's broth cultures on blood agar plates to separate the smooth and rough variants.…”
Section: Discussionmentioning
confidence: 99%
“…It was felt that similar changes occurred in yeast-like fungi and might account for many of the irregularities noted in descriptions based on studies of old strains. Martin and Jones (1940), for example, observed that about one-fourth of the strains of Candida2 obtained from the Centraalbureau voor Schimmelcultures differed from the original descriptions in certain features. While it was thought that these cultures were members of the six species described by them, they could be classified only provisionally by the methods adapted to the study of freshly isolated strains.…”
Section: Introductionmentioning
confidence: 99%